Pendekatan Non-Penal Dalam Upaya Deradikalisme di Lingkungan Kampus - Sufyan Sufyan; Khaerul Wahidin; Muhammad Azka Maulana (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2022)
The presence of radicalism is increasingly alarming and is a form of activity that all communities are aware of because the precursor of this radicalism increasingly thrives in the community. Like many acts of vigilanties, organized violence, down to the anarchistic way of conveying thoughts and opinions and responding to the differences in the neighborhood have become the people's everyday food. It is therefore essential to counter radicalism. The good news is that many deradicalism movements have been carried out today. One of the most pervasive deradicalism activities is the campus radicalism prevention effort. The deradicalism movement in the university's environment is intended for Indonesian students to gain early knowledge about radicalism that can occur in community life, especially in the campus environment. The purpose of the study is to see the existence of the non-penal approach on the campus of radicalism. The more special non-penal approach on these studies focuses on optimizing some of the roles of religious and state subjects. The study was conducted by a quantitative approach with a type of angket data that included 51 respondents from various colleges in indonesia. Non-penal approaches have been optimized by leverages of these premier and state institutions, namely, have been widely implemented in universities in Indonesia. In addition to optimizing classes, many other efforts are made by the campus, depending on individual policies.